Analysis and Characterization of Composites for their potential use in Disc Brake Pad - Fouzia Gillani; Umer Ijaz; Muhammad Fraz Anwar; Muhammad Saad Sharif; Ali Iqbal; Rana Hassan Ali (Sir Syed University Research Journal of Engineering and Technology)
Brake pads are crucial for vehicle safety, converting kinetic energy to halt motion. They come in types like organic, semi-metallic, ceramic, and metallic. Beyond automotive, brake pads find application in industries such as aerospace, railways, manufacturing, and wind energy for controlled deceleration and safety. This study is primarily concerned with the quality and appropriateness of ceramic brake pads for automotive applications, which are an essential aspect of braking systems for vehicles. The performance characteristics of ceramic brake pads are well established, and this study explores the variables affecting their quality. Under high pressure, brake pad samples are prepared in the study using Powder Metallurgy (PM), which guarantees superior mechanical qualities by removing interface bonding problems. The samples are then sintered at 2850. Hardness, temperature resistance, wear resistance, and Electron Dispersive Spectroscopy (EDS) analysis are all included in the evaluation to ascertain the make-up and distribution of the materials in the brake pad. EDS sheds light on the degree of sintering and the presence of reinforcements. Heat resistance is evaluated using controlled thermal testing, while wear resistance and hardness are determined through Rockwell hardness testing and wear tests, respectively. These measurements are validated for use in automotive disc braking systems for vehicles and motorcycles. The findings are more reliable thanks to statistical analysis done with MINITAB. The study highlights research gaps in environmentally friendly materials, emerging technology impacts, and long-term brake pad durability.